Fires in Pantanal: The link to Agriculture, Conversions in Cerrado, and Hydrological Changes - Santos, Fabrícia Cristina [UNESP]; Chaves, Fellipe Mira [UNESP]; Negri, Rogério Galante [UNESP]; Massi, Klécia Gili [UNESP] (My University, 2024)
Wildfires and deforestation are severe threats to global ecosystems. In Brazil, Cerrado (a tropical savanna) and Pantanal (a tropical wetland) biomes have undergone several changes over the years due to anthropic actions. Both deforestation in Cerrado biome and wildfires in Pantanal have increased lately. Some studies argue that both processes could be related, but there is a scarcity of quantitative analysis evaluating that. In this context, making use of machine learning techniques and temporal data obtained by Remote Sensing in the period 2000–2020, this study aimed to identify the interactions between Cerrado land use and land cover change in native vegetation and wildfires incidence in Pantanal. Our results corroborate that and show that wildfires in Pantanal were directly linked to large-scale and commodities agriculture conversion in Cerrado, as well as native vegetation loss and hydrological changes in Pantanal.
Keywords: Cerrado; Machine Learning; Pantanal; Remote Sensing; Times Series; Wildfires